Role of a heart valve clinic programme in the management of patients with aortic stenosis. (12th August 2016) - Zilberszac, Robert; Lancellotti, Patrizio; Gilon, Dan; Gabriel, Harald; Schemper, Michael; Maurer, Gerald; Massetti, Massimo; Rosenhek, Raphael
Abstract : Aims: We sought to assess the efficacy of a heart valve clinic (HVC) follow-up programme for patients with severe aortic stenosis (AS). Methods and results: Three hundred and eighty-eight consecutive patients with AS (age 71 ± 10 years; aortic-jet velocity 5.1 ± 0.6 m/s) and an indication for aortic valve replacement (AVR) were included. Of these, 290 patients presented with an indication for surgery at their first visit at the HVC and 98 asymptomatic patients who had been enrolled in an HVC monitoring programme developed indications for surgery during follow-up. Time to symptom detection was significantly longer in patients that presented with symptoms at baseline (352 ± 471 days) than in patients followed in the HVC (76 ± 75 days, P < 0.001). Despite being educated to recognize and promptly report new symptoms, 77 of the 98 patients in the HVC programme waited until the next scheduled consultation to report them. Severe symptom onset (NYHA or CCS Class ≥III) was present in 61% of patients being symptomatic at the initial visit and in 34% of patients in the HVC programme ( P < 0.001). Conclusion: Delays in referral and symptom reporting as well as symptom denial are common in patients with AS. These findings support the concept of risk stratification to identify patients who may benefit from elective surgery. A structured HVC programme results in the detection of symptoms at an earlier and less severe stage and thus in an optimized timing of surgery.